2015
DOI: 10.1080/01652176.2015.1055352
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral analysis of urine proteomic profiles of dairy cows suffering from clinical ketosis

Abstract: (2015) Mass spectral analysis of urine proteomic profiles of dairy cows suffering from clinical ketosis, Veterinary Quarterly, 35:3,[133][134][135][136][137][138][139][140][141]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…A comparative proteomic assessment of liver proteins and 5 enzymes (i.e., acetyl-coenzyme A acetyltransferase 2, 3-hydroxyacyl-CoA dehydrogenase type-2, elongation factor Tu, alpha-enolase and creatine kinase) revealed that they were differentially expressed in ketotic cows compared with healthy controls [54]. Moreover, urine concentrations of 11 proteins including amyloid precursor protein, apolipoprotein (Apo) C-III, cystatin C, fibrinogen, hepcidin, human neutrophil peptides, osteopontin, VGF (non-acronymic) protein, serum amyloid A (SAA), the C1 inhibitor (C1INH), and transthyretin were decreased in ketotic cows [55]. The same authors reported that serum fibroblast growth factor-21 might be a promising biomarker for detecting ketotic cows [56].…”
Section: Some Newly Identified Diagnostic Biomarkersmentioning
confidence: 99%
“…A comparative proteomic assessment of liver proteins and 5 enzymes (i.e., acetyl-coenzyme A acetyltransferase 2, 3-hydroxyacyl-CoA dehydrogenase type-2, elongation factor Tu, alpha-enolase and creatine kinase) revealed that they were differentially expressed in ketotic cows compared with healthy controls [54]. Moreover, urine concentrations of 11 proteins including amyloid precursor protein, apolipoprotein (Apo) C-III, cystatin C, fibrinogen, hepcidin, human neutrophil peptides, osteopontin, VGF (non-acronymic) protein, serum amyloid A (SAA), the C1 inhibitor (C1INH), and transthyretin were decreased in ketotic cows [55]. The same authors reported that serum fibroblast growth factor-21 might be a promising biomarker for detecting ketotic cows [56].…”
Section: Some Newly Identified Diagnostic Biomarkersmentioning
confidence: 99%
“…Meanwhile, a link between clinical ketosis in dairy cows and decreased milk production, rumen stagnation, constipation, decreased feed intake, as well as loss of body condition, and an association between hyperketosis and increased levels of oxidative stress has also been revealed [3]. Ketogenic cows have a lower milk yield, lower milk fat content, and higher concentrations of BHBA, NEFAs, interleukin (IL)-6, tumor necrosis factor (TNF), and lactic acid in serum compared with healthy cows [4,5,6], and the antioxidant capacity of ketone-causing bovine bodies is also greatly reduced [7]. High levels of NEFAs and BHBA are also associated with inflammatory responses during diseases such as cow mastitis and metritis.…”
Section: Introductionmentioning
confidence: 99%
“…One estrogen metabolite, not further specified, was found to discriminate between mild or strong and weak fatty liver in the same study. Beside liver and plasma, the difference of proteomic profiles in animals with ketosis were also explored in urine using SELDI-TOF techniques [91]. Samples were collected 7 -28 DIM from two groups of animals, one affected by clinical ketosis and the other from healthy cows, with a milk production of 9625 kg/year.…”
Section: Fatty Livermentioning
confidence: 99%